Peer Acceptance of Students with Hearing Disorders in Inclusive and Non-Inclusive Schools - Narges Adib-Sereshki; Yeganeh Saleh-Pour (University of Social Welfare and Rehabilitation Sciences, 2004)
Objective: This study investigated the level of hearing disorder children's acceptance by their peers in inlusive and non-inclusive schools in the city of Tehran. Materials & Methods: The sample in this study was 323 elementary school students in grades 3-5 from the schools in different regions of Tehran. These students were studying alongside their peers with mild hearing disability. Also for comparison this study used a sample of 65 students from non-inclusive (regular) schools. Level of acceptance was measured through the use of Acceptance Scale developed by Voeltz (1980). The major questions in this study were based on the impact of the following factors, gender and the type of schools attended by students (inclusive or non-inclusive). Results: The results indicated that in inclusive schools, boys level of acceptance were higher than that of the girls. Also a significantly lower level of acceptance was found in regular school students as compared with that found in inclusive schools. Conclusion: This finding led the investigators to conclude that the experience of inclusive education can lead to higher level of regular students' acceptance towards special need students. Suggestions for future research are given in light of limitations of present research and the need for further understanding of the factors contributing to student acceptance in inclusive settings is emphasized.